Patients with Diabetes Complicated by Peripheral Artery Disease: the Current State of Knowledge on Physiotherapy Interventions - Katarzyna Hap; Karolina Biernat; Grzegorz Konieczny (Journal of Diabetes Research)
Diabetes mellitus (DM) is one of the major public health problems that account for morbidity, mortality, and disability worldwide. The presence of DM increases the risk of peripheral artery disease (PAD), as well as accelerates its course, making these patients more susceptible to ischemic events and impaired functional status. Unfortunately, alternative treatments for vascular complications in diabetes are poorly researched. Physiotherapy (kinesitherapy combined with different physical therapy agents) in individuals with DM and coexisting PAD may offer an important complementary therapy alternative. Early therapeutic measures can significantly improve patient outcomes, reduce cardiovascular risk, and improve daily life quality. The article provides an update on the current state of knowledge on physiotherapy interventions in the course of DM in patients with coexisting PAD.